UJI PERTUMBUHAN AWAL BIBIT KOPI ROBUSTA (COFFEA CANEPHORA) YANG DIBERI PERLAKUAN KONSENTRASI PUPUK ORGANIK CAIR (POC) DAN INTENSITAS NAUNGAN - Novianto, Arif Nur; Budirokhman, Dodi; Nur, Subandi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2024)
The research was purposed to know the influence concentration of liquid organic fertilizer and shade intensity to growth of robusta coffee seedlings. Research was conducted in Cibeureum, Cilimus, Kunigan district. Research was conducted on January – May 2018. The experimental metode used is split plot design, which consist two factors. First factor is the shade intensity which consist of level that are shade 50% (N1), shade 75 % (N2) and shade 95 % (N3). The second factor is concentration of liquid organic fertilizer consist 3 level, 0 ml/l water (P1), 400 ml/l water (P2) and 800 ml/l water (P3). All of treatments were repeated 3 times, that there are 27 experimental unit. The observation variables were increase in plant height, increase in leaf number, increase in stem diameter, root volume and dry weight of plants. The date observation result then do analysis of variance test F real level 5%. if there is a real difference, then the test continued with Least Significance Different on level 5%. The result showed that there was an interaction between giving concentration of liquid organic fertilizer and shade intensity to parameters of the average yield of plants aged 60 HSPT and dry weight of plants. In additin, this treatment independently affects the parameters of the average yield of plants 30, 90 and 120 HSPT, the average increase in stem daimeter od 60, 90 and 120 HSPT, and the average root volume.